(untitled) (Malaysian Journal of Learning and Instruction, 2024)
Purpose – Many students perceive plant anatomy as difficult due to the complexity of the material. Additionally, conventional teaching techniques often neglect the importance of information retention in the learning process. Therefore, this study examines the effects of Retention-Based Learning on students’ learning outcomes compared to conventional learning without Retention-Based Learning. Methodology – A multiple-group time series research design was used to measure the effectiveness of Retention-Based Learning on students’ learning outcomes including information retention, cognitive load, and learning achievement. Retention interventions in the Retention- Based Learning class included watching videos, identifying images and answering questions. The participants in this study were seventyeight 10th-grade public high school students in Bandung, West Java, Indonesia, divided into two research groups. Findings – This study found that students in the experimental group had better information retention in each lesson and a significantly higher ability to process information with less mental effort and lower cognitive load than the control group. Additionally, the experimental group showed significantly higher learning achievement than the control group. These findings demonstrate the importance of maintaining information retention to maximize learning outcomes in plant anatomy lessons. Significance – This study indicates that maintaining retention can be a simple and powerful learning approach to help high school teachers teach complex material. The study highlights the significance of maintaining student retention to improve learning performance.